Result Based approach on Intrusion Detection System against Sinkhole Attack in Wireless Sensor Networks - Aggarwal, Rohit; Bansal, Khushboo (International Journal of Computer Sciences and Engineering, 2025)
The main problem in the proposed work was the sinkhole attack which was detected and removed by implementing appropriate protocol such as AODV i.e. ad hoc on-demand distance vector (AODV) routing. In this paper, eliminate the sinkhole attack from network by using a novel algorithm for sinkhole detection. The algorithm first finds a list of suspected nodes through checking data consistency and then effectively identifies the intruder in the list through analyzing the network flow information. The algorithm is also robust to deal with multiple malicious nodes that cooperatively hide the real intruder.